Investigating the Effect of TV Advertising Strategies on Cognitive, Emotional and Behavioral Dimensions of Female Consumer Attitudes - Afsaneh Javan Hesar Shaneh; Naser Yazdani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The primary purpose of this study is to investigate the effect of television advertising strategies on the cognitive, emotional, and behavioural dimensions of female consumers' attitudes.Methodology: The study is a descriptive survey in terms of implementation methods. The statistical population in this study are all female consumers of detergent and hygiene products of three brands (Golrang, Softlan, and Active) offered in OK chain stores in Tehran. The number of samples equals 384 people due to the unlimited statistical population. The sampling method is a cluster random method. The data collection tool is a researcher-made questionnaire using the Kaur & Hundal (2017) questionnaire distributed among the sample members after validation and reliability assessment. The collected data were analyzed using SPSS and AMOS software.Findings: The results showed that TV advertising strategies affect female consumers' cognitive, emotional, and behavioural dimensions. Examining the sub-hypotheses showed that repetition of advertisements, approval of celebrities, gender attractions, humorous characters, and product comparison affect female consumers' cognitive and emotional attitudes. Also, cognitive attitude affects shopping behaviour and changes consumer behaviour, and emotional attitude significantly changes shopping behaviour. Among the hypotheses presented in the research, the results showed that emotional attitude has no significant effect on female consumers' shopping behaviour.Originality/Value: TV advertising strategies will affect different dimensions of women consumers' cognitive, emotional, and behavioural attitudes towards detergents and hygiene products and lead to different shopping behaviours